2018
DOI: 10.26656/fr.2017.3(1).221
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adjunct inoculation of Lactobacillus plantarum BS and Pediococcus acidilactici 3G3 on the microbiological, physicochemical and sensory properties of fermented carabeef (pindang damulag)

Abstract: Lactobacillus plantarum BS and Pediococcus acidilactici 3G3 were inoculated singly or jointly on carabeef (pindang damulag) and allowed to ferment at 10 and 32°C for five days, in comparison with uninoculated naturally fermenting samples. Greater pH reduction and increased lactic acid production was observed in samples inoculated with the lactic acid bacteria (LAB) starter cultures and those fermented at 32°C. Fermentation increased the monounsaturated fatty acid content of carabeef which may have good health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A previous study identified P. acidilactici 3G3, which was isolated from Philippine fermented pork, as a promising candidate for probiotic food applications ( 2 ). Furthermore, this strain significantly improved the safety and nutritional and sensory properties of pindang damulag (fermented carabeef) ( 3 ). Evaluating its safety and probiotic potential using whole-genome sequencing is essential for the development of novel functional food products and starter cultures.…”
Section: Announcementmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study identified P. acidilactici 3G3, which was isolated from Philippine fermented pork, as a promising candidate for probiotic food applications ( 2 ). Furthermore, this strain significantly improved the safety and nutritional and sensory properties of pindang damulag (fermented carabeef) ( 3 ). Evaluating its safety and probiotic potential using whole-genome sequencing is essential for the development of novel functional food products and starter cultures.…”
Section: Announcementmentioning
confidence: 99%
“…P. acidilactici 3G3 was previously isolated from burong babi , a fermented pork dish, obtained from a wet market in Pampanga, Philippines ( 3 ). We obtained the strain from the collection of the Food and Feeds Laboratory of the National Institute of Molecular Biology and Biotechnology, University of the Philippines Los Baños (Laguna, Philippines).…”
Section: Announcementmentioning
confidence: 99%
“…To determine the total viable lactobacilli count, the standard plate count method was employed. The samples were plated on MRS agar and subjected to incubation at 37 • C for a duration of 48 h. Following incubation, the number of colony-forming units per mL was enumerated using the methodology described by a previous report [17]. Both analyses were performed in triplicate.…”
Section: Enumeration Of Viable Lactobacillimentioning
confidence: 99%